Au-catalyzed biaryl coupling to generate 5- to 9-membered rings: turnover-limiting reductive elimination versus π-complexation - Corrie, Tom J.A.; Ball, Liam T.; Russell, Christopher A.; Lloyd-Jones, Guy C. (American Chemical Society, 2016)
The intramolecular gold–catalyzed arylation of arenes by aryltrimethylsilanes has been investigated from both a mechanistic and preparative aspect. The reaction generates five to nine membered rings, and of the 44 examples studied, ten include a heteroatom (N, O). The tethering of the arene to the arylsilane not only provides a tool to probe the impact of the conforma-tional flexibility of Ar–Au–Ar intermediates, via systematic modulation of the length of aryl-aryl linkage, but also the ability to arylate neutral and electron-poor arenes - substrates that do not react at all in the intermolecular process. Rendering the arylation intramolecular also results in phenomenologically simpler reaction kinetics, and overall these features have facili-tated a detailed study of linear free energy relationships, kinetic isotope effects, and the first quantitative experimental data on the effects of aryl electron-demand and conformational freedom on the rate of reductive elimination from diaryl gold(III) species. The turnover-limiting step for the formation of a series of fluorene derivatives is sensitive to the electronics of the arene and changes from reductive elimination to π-complexation for arenes bearing strongly electron-withdrawing substitu-ents (σ >0.43). Reductive elimination is accelerated by electron-donating substituents (□ = -2.0) on one or both rings, with the individual σ-values being additive in nature. Longer and more flexible tethers between the two aryl rings results in faster reductive elimination from Ar-Au(X)-Ar, and to the π-complexation of the arene by Ar-AuX2 becoming the turnover-limiting step.